2011
DOI: 10.1038/nm.2337
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic modulation of the renal β-adrenergic–WNK4 pathway in salt-sensitive hypertension

Abstract: How high salt intake increases blood pressure is a key question in the study of hypertension. Salt intake induces increased renal sympathetic activity resulting in sodium retention. However, the mechanisms underlying the sympathetic control of renal sodium excretion remain unclear. In this study, we found that β(2)-adrenergic receptor (β(2)AR) stimulation led to decreased transcription of the gene encoding WNK4, a regulator of sodium reabsorption. β(2)AR stimulation resulted in cyclic AMP-dependent inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(210 citation statements)
references
References 50 publications
11
193
0
3
Order By: Relevance
“…WNK4 expression alone inhibits NCC (17,18,27,56) and does not result in stimulation of the Ste20-related proline alanine rich kinase−NCC cascade and Na + reabsorption (27). AII might also induce phosphorylation of WNKs, thereby modulating the activity of electrolyte flux pathways.…”
Section: Discussionmentioning
confidence: 99%
“…WNK4 expression alone inhibits NCC (17,18,27,56) and does not result in stimulation of the Ste20-related proline alanine rich kinase−NCC cascade and Na + reabsorption (27). AII might also induce phosphorylation of WNKs, thereby modulating the activity of electrolyte flux pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenergic receptor activation inhibits WNK4 expression and induces NCC expression, and it increases sodium retention in renal distal convoluted tubes. This increase of sodium retention leads to higher blood pressure in the end (Mu et al, 2011). We thus postulate that the inhibition of NCC expression by BS and PBS would be an autonomic nervous system independent mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…Increase in NCC induces increase of sodium retention, and it is critical in the blood pressure increase. NCC expression in distal convoluted tubes is suppressed by WNK4 (Mu et al, 2011). To investigate the effects of BS and PBS on distal convoluted tubes' NCC mRNA expression, we performed the RT-PCR.…”
Section: Bs and Pbs Inhibited Ncc Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 For example, an important recent study has shown that beta(2)-adrenergic stimulation causes inhibition of histone deacetylase-8 activity and suppression of WNK4, a regulator of sodium reabsorption. 9 Another study has suggested that statins may also cause epigenetic modification of multiple genes. 10 Taken together, these results suggest that multiple dynamic interactions between the genes and the environment, including biochemical, structural and epigenetic changes, may be involved in the mechanisms of the memory/legacy effect (Figure 1).…”
mentioning
confidence: 99%